A landscape transformed : the ironmaking district of Salisbury, Connecticut - Gordon, Robert B. (Robert Boyd), 1929- (Oxford Univ. Press, 2001)
This book examines the industrial ecology of 200 years of ironmaking with renewal energy resources in northwestern Connecticut. It focuses on the cultural context of people's decisions about technology and the environment, and the gradual transition they effected in their land from industrial landscape to pastoral countryside.